2005
DOI: 10.4049/jimmunol.175.10.6633
|View full text |Cite
|
Sign up to set email alerts
|

RNA Stability of the E2A-Encoded Transcription Factor E47 Is Lower in Splenic Activated B Cells from Aged Mice

Abstract: We have demonstrated previously that DNA binding and protein expression of the E2A-encoded transcription factor E47 are lower in nuclear extracts of activated splenic B cells from old mice. In the present study, we address how E47 protein expression is regulated in aging. Results herein show that E2A mRNA levels were decreased in stimulated splenic B cells from old as compared with young mice. RNA stability assays showed that the rate of E2A mRNA decay was accelerated in stimulated splenic B cells from old mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 77 publications
5
42
0
Order By: Relevance
“…All the experiments herein have been done with females. Our previous studies (Frasca et al, 2005) indicated no significant differences between females and males with regard to aging defects.…”
Section: Micementioning
confidence: 75%
“…All the experiments herein have been done with females. Our previous studies (Frasca et al, 2005) indicated no significant differences between females and males with regard to aging defects.…”
Section: Micementioning
confidence: 75%
“…These eight Ct differences were used to normalize the targeted genes. Thus, though RNA degradation is a characteristic of aged spleen RNA which is more sensitive than the young one to degradation (Frasca et al 2005) it could be normalized by the use of the multiple housekeeping genes. No Ct difference was found in total RNA from livers obtained from young and old rats.…”
Section: Mcrc Proteinsmentioning
confidence: 99%
“…We have previously shown that, in senescence, posttranscriptional mechanisms in B cell precursors generate reduced E47 protein expression (12); however, in activated splenic B cells reduced E47 mRNA stability is responsible for lower levels of E47 protein (13). In a recent report (14), the degradation of E47 proteins in lymphocytes was shown to be promoted by serine/threonine MAPKs and to be highly dependent upon activation of the Notch pathway.…”
mentioning
confidence: 97%